Biomechanical stress distribution on fixation screws used in bilateral sagittal split ramus osteotomy: Assessment of 9 methods via finite element method - Bohluli, B.; Motamedi, M.H.K..; Bohluli, P.; Sarkarat, F.; Moharamnejad, N.; Tabrizi, M.H.S. (Elsevier, 2010)
Purpose: The aim of this study was to assess the biomechanical stress tolerance of screws used in 9 fixation methods after bilateral sagittal split ramus osteotomy to determine which configuration leads to lesser force load on the cortical bone at fixation points. Materials and Methods: A 3-dimensional computerized model of a human mandible with posterior teeth was generated. The bilateral sagittal split ramus osteotomy was virtually performed on this model. The separated model was assembled with 9 fixation methods: single screw, 2 screws one behind the other, 2 screws one below the other, 3 screws in an L configuration, 3 screws in an inverted backward L configuration, miniplate with 2 screws, miniplate with 4 screws, 2 parallel plates (upper + lower border), and square miniplate with 4 screws. Then, 75-, 135-, and 600-N vertical loads were applied on the posterior teeth of these models. The stress distribution on the screw sites on the buccal cortex was measured by the finite element method. Results: In this model all the fixation methods withstood forces between 75 and 135 N. However, the single-screw and the 2-hole miniplate models showed that the stress distributions in the configurations were intolerable when 600 N of posterior force was applied. The results of this study indicated that the inverted backward L configuration with 3 bicortical screws was the most stable. Conclusion: Although this study indicated that the inverted backward L configuration with 3 bicortical screws was the most stable pattern, most of the patterns had adequate stability for clinical applications (mean, 125 N). (c) 2010 American Association of Oral and Maxillofacial Surgeons J Oral Maxillofac Surg 68:2765-2769, 2010